Worldviews in Conflict: Negotiating to Bridge the Divide. Issue 3 (15th August 2022) - Shapiro, Daniel L.; Iwry, Jonathan
Abstract : Many global and political conflicts involve differences in worldviews. As our world grows increasingly interconnected, and as differences in identity—and the politics of identity—play an increasingly prominent role in our cultural discourse, these differences become harder than ever to ignore. Yet worldviews remain poorly understood, and traditional methods of interest‐based negotiation are insufficient to address this dimension of conflict, which implicates core aspects of who we are, what we believe, and how we make meaning in the world. In this article, we examine what worldviews are, why they matter, and how clashes of worldviews can impede conflict resolution. We offer strategies and tactics to overcome these obstacles, drawing on scholarship in conflict management, social identity theory, relational identity theory, and moral psychology. Overcoming the clash of worldviews requires that we learn to build bridges across our respective worldviews, acknowledging each party's relationship to their beliefs and values while emphasizing similarities to build a common identity that transcends our respective differences.